Reducing weldline in plastic injection molding - Thi Hong, Minh Nguyen
Weldlines in plastic injection molding occur at the point where two different flow fronts meet, which can be caused by inserts, lattices, or multi-point gates. The presence of weld lines in areas of stress concentrations may lead to strength problems, and therefore, countermeasures should be implemented in advance. This paper addresses a method of reducing weldline problems which takes into account the important process parameters that impact the weldlines such as the mold and the melt temperature, as well as the injection speed. Using experimental approach, quantifying the weldline in parts produced under different conditions reveals that it is possible to reduce the weldline size by adapting the process parameters, where the melt temperature plays the most important role. Such data has been used to optimize the injection condition which can offer minimal weldline width of 0.8 m for a specific case.
Keywords: Injection molding; Plastic; Process parameter optimization